Environmental fluctuation impacted the evolution of Early Pleistocene non-human primates: Biomarker and geochemical evidence from Mohui Cave (Bubing, Guangxi, southern China). (20th October 2020) - Cheng, Liuling; Bae, Christopher J.; Hong, Hanlie; Huang, Shengmin; Wang, Wei; Yin, Ke; Wang, Chaowen
Abstract: Quaternary climate variability, profoundly impacting the evolution and distribution of plants and animals across the globe, has been reconstructed by many sediment archives. Here, we track past changes of temperature, rainfall and plant type by using the n-alkane and glycerol dialkyl glycerol tetraethers (GDGTs), as well as weathering and pedogenesis by mineralogical and geochemical proxies from a 250 cm deep soil sediment profile from the Early Pleistocene deposits in Mohui Cave, southern China. Indices for weathering intensity such as mineral composition (quartz, feldspar and calcite), major element proxies (Ti/Na, Al/Na, Al/Mg, Ti/Mg, CIW, PIA, CPA, CIA), trace element proxies (Ba/Sr and Rb/Sr), and biomarker proxies (OEP, LSR and CPI) show similar secular trends, revealing a three-stage historical accumulation. The high long-chain n-alkane ratios (C31 /C29 and (C31 +C33 )/(C27 +C29 )) indicate that the vegetation in the region had increases in percentage of woody plants and decreases in herbs during periods of relatively lower temperature and less precipitation, which evidenced from GDGTs, consistent with a weak weathering process influenced by summer monsoon strength. Further, we compared the distribution of these plant types with the taxonomic variation in the vertebrate paleontological fossils excavated from the same profile in Mohui Cave. The distribution of Lufengpithecus appears in only one interval but Gigantopithecus blacki appears throughout the profile, despite an environment that experienced transitional stages from grassland to woodland in relatively cooler and drier conditions. We infer that in face of these climatic changes Lufengpithecus may have preferred to emigrate from the region, while Gigantopithecus blacki may have stayed given that it was limited to staying in its core area.